Regional Personality Variation in Sweden: Trait Clusters, Links to Health and Well-Being, and Historical Context - Obschonka, Martin; Grillitsch, Markus ; 0000-0002-8406-4727; Guldåker, Nicklas ; 0000-0002-5711-9091; Rauhut, Daniel; Jason Rentfrow, Peter; Potter, Jeff; Gosling, Samuel D. (Scandinavian Journal of Psychology, 2025)
Personality traits (e.g., the Big Five) shape human behavior, decision-making, and life outcomes. Evidence from various countries suggests that these traits are not randomly distributed but follow systematic regional patterns, fueling interest in their geographical variation. We analyze N = 22,225 geo-coded personality assessments, aggregated at regional levels. Using Hot Spot analysis (Getis-Ord Gi), we identify spatial clusters of personality traits and test their associations with health and well-being indicators at the regional level. Even though Sweden has a reputation for equality, our analysis reveals notable spatial differences in personality composition. The data reveal overlapping geographical clustering in Extraversion, Conscientiousness, and Emotional Stability (i.e., low Neuroticism), traits that are established predictors of better psychological functioning. These traits co-occur at relatively higher levels in southern Sweden, particularly in the Scania region, whereas they co-occur at relatively lower levels in parts of central Sweden. These patterns are descriptively supported by municipal-level correlations with health and well-being variables, although the associations are not uniform across all measures. In view of these results, we reflect on how these clusters may connect to long-standing regional histories, including industrial legacies. Such interpretations remain speculative, and we outline a future research agenda to further investigate the causes and consequences of regional personality variation, as well as its possible societal implications.
Keywords: culture; conomic history; geography; personality; regions; Sweden